Glorifying Cultural Scapes to Conflictual Tourismscapes: the Dynamics of Tourism Development in Rural Indonesia - Widiastuti, Rina; Richardus, Wisma Nugraha Christianto; Budiawan, Budiawan (E-Journal of Tourism; Volume 9 Number 1 (March 2022), 2022)
This article discusses the cultural village transformation into a tourism village in Bejiharjo, a rural tourism destination in Indonesia. Based on the Actor-Network Theory, Bejiharjo is a space formed in a dynamic network of relationships between actors, both human and non-human actors. Using online media observation, semi-structured interviews, and direct observation, the complexity of the relations between actors in the transformation of rural development that causes aestheticisation, consumerism, translation, place-making, touristification, and cosmopolitanism in Bejiharjo is explored. The findings of this study reveal that, at first, the cultural scapes ordering of Bejiharjo should conserve local cultural values. Then, government regulations on tourism development emerged and encouraged the development of rural areas with the concept of a tourism village. This dynamic and interrelated process triggers competition between individual and group interests and causes chronic conflicts in Bejiharjo.